The experience of thesis writing in terms of the methodological students' digital competence development (Educational Dimension, 2022)
In the context of digital technologies' development, digital competence is a necessary prerequisite for everyone to learn, work, and actively participate in social life. Higher education institutions are faced with the mission of selecting and developing appropriate teaching strategies and cultivating digital competencies of students and academics, as well as using appropriate tools to improve the quality of education. The article highlights the experience of forming digital competencies among students majoring in the 122 Computer Science specialization while writing their thesis. Students developed a university automated system for choosing disciplines from the variable part of the curriculum. The practical results obtained by students during the research in accordance with the thesis tasks are represented by the following: examples of UML and ER diagrams (design stages), graph images (implementation stage), sections of the program code and test results of the created automated system (implementation and configuration stages of the software product). The formation and development of digital competencies during such thesis research is analyzed. The European model of digital competencies "The Digital Competence Framework for Citizens" (DigComp 2.1) has been selected as a conceptual standard. Attention is focused on three areas of DigComp 2.1: information and data literacy; digital content creation; problems solving in the digital environment. The activities that contribute to the formation of these competencies are outlined. It is concluded that the described strategy promotes the formation and development of digital competence at the eighth (highest) professional level in accordance with the DigComp 2.1 model for higher education students majoring in the 122 Computer Science specialization.